Adherence Scale to the Recommendations for Mental Health during the COVID-19 pandemic from the Portuguese General Directorate of Health (ASR-MH-COVID19) - Development and validation. (1st June 2022) - Pereira, A.T.; Cabacos, C.; Soares, S.; Pacheco, M.J.; Manão, A.; Araújo, A.; Amaral, A.P.; De Sousa, R.; Macedo, A.
Abstract : Introduction: The COVID-19 crisis has generated an increasing stress throughout the population. Objectives: To develop and validate the A dherence S cale to the R ecommendations for M ental H ealth during the COVID-19 pandemic from the Portuguese G eneral D irectorate of H ealth (GDH) (ASR-MH-COVID19). Methods: The items content was based on the GDH guides for the prevention of mental health and psychosocial well-being of the general population during the COVID-19 outbreak. After content and facial validity analysis, the preliminary version of the ASR-MH-COVID19 (8 items to be answered on a Likert scale) was completed by 413 individuals (69.2% female; mean age=31.02±14, 272), in September-December 2020 (Sample1) and then by 967 (70.9% female; mean age=34.02±14, 272), in February-May 2021 (Sample2). Sample1 was randomly divided in two sub-samples. Sample1A was used for exploratory factor analysis/EFA and Sample1B for confirmatory factor analysis/CFA; CFA was then replicated with Sample2. The online surveys also included the A dherence S cale to the R ecommendations of Portuguese GDH to minimize the impact of COVID-19 (ASR-COVID-19; Pereira et al. 2020). Results: CFAs were informed by EFA and showed that the unidimensional model presented acceptable-good fit indexes (Sample1B: χ 2 /df=2.747; RMSEA=.0980, p<.001; CFI=.973; TLI=.918, GFI=.972; Sample2: χ 2 /df=3.327; RMSEA=.0490, p<.001; CFI=.993; TLI=.983, GFI=.990). Cronbach's alfas were α<.850. Pearson correlations between ASR-MH-COVID19 and ASR-COVID19 were significant (p<.01) and moderate-high for the total (r=.753) and dimensional scores (Distance and respiratory hygiene, r=.739; House and personal hygiene, r=.584; Use of remote services and isolation r=.425). Conclusions: The new ASR-MH-COVID19 has shown validity and reliability, allowing the investigation of this (mental) health behaviour. Disclosure: No significant relationships.